2014
DOI: 10.1186/1471-2474-15-249
|View full text |Cite
|
Sign up to set email alerts
|

Identification of initial severity determinants to predict arthritis after chikungunya infection in a cohort of French gendarmes

Abstract: BackgroundThe objective was to identify severity characteristics of initial chikungunya infection (CHIKV) stages associated with post-CHIKV arthritis and arthralgia.MethodsFrench gendarmes exposed to the 2005–2006 CHIKV epidemic in Reunion Island who completed the 2006 (self-reporting acute and early chronic [median: 6 months] symptoms) and 2008 (Endpoint [median: 30 months]: self-perceived recovery and rheumatic disorders (RDs)) surveys were included. Multinomial logistic regression and multiple correspondenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 17 publications
1
28
0
2
Order By: Relevance
“…In an outbreak in Italy, Moro et al reported that IgM was detected in 52% (131/249) of patients within 5 months of the contracting disease and in 13.2% (30/227) with 12 months of disease evolution (17) . Other risk factors associated with progression to a chronic form include age >35 years, marked joint impairment in the acute phase, and pre-existing prior joint disease (4) (9) (18) . Some patients have polymorphisms of the human leukocyte antigens (HLA) that are associated with rheumatic diseases, such as HLA-27.…”
Section: The Pathophysiology Of the Pain Of Chikungunyamentioning
confidence: 99%
“…In an outbreak in Italy, Moro et al reported that IgM was detected in 52% (131/249) of patients within 5 months of the contracting disease and in 13.2% (30/227) with 12 months of disease evolution (17) . Other risk factors associated with progression to a chronic form include age >35 years, marked joint impairment in the acute phase, and pre-existing prior joint disease (4) (9) (18) . Some patients have polymorphisms of the human leukocyte antigens (HLA) that are associated with rheumatic diseases, such as HLA-27.…”
Section: The Pathophysiology Of the Pain Of Chikungunyamentioning
confidence: 99%
“…The presence of immunoglobulin M (IgM) antibodies detected months after the acute infection suggests persistence of the virus or its antigens; this may perpetuate the inflammatory process in the joints. 41,44 In an outbreak in Italy, Moro et al reported that IgM was detected in 52% (131/249) of patients within 5 months of the contracting disease and in 13. 2% (30/227) with 12 months of disease evolution 42 .…”
Section: Figmentioning
confidence: 99%
“…A classical switch from CD+ 8 cell to CD4+ T-cell response and the production of anti-inflammatory proteins IL-1RA and IL-they do not directly depend on an inflammatory processes, but involve specific changes in central and peripheral nociceptive processes. 44 Therefore, it seems that the mechanisms are multifactorial and may different between patients. A clear understanding of the pathophysiologic mechanisms in patients with Chikungunya will have a direct bearing on the choice of ideal therapeutic agent to relieve the pain.…”
Section: Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Guidelines advocate specialists sharing responsibility with GPs. 57% of rheumatologists considered GPs responsible (2). Perhaps, we should take a more active approach.…”
mentioning
confidence: 99%